Narrative Politics in Policy Discourse: The Debate Over Safe Injection Sites in Philadelphia, Pennsylvania. (March 2021) - Lofaro, Ryan J.; Miller, Hugh T.
Safe injection sites are spaces where people who inject drugs can do so under the supervision of staff at the sites who attempt to revive them if they overdose. Public officials in Philadelphia, Pennsylvania, have proposed the sites as a means to reduce opioid overdose deaths in the city, a policy proposal that has been politically and legally contested. This article uses the Narrative Politics model to elucidate the concerns, values, and aspirations of the competing narratives in the public discourse over safe injection sites in Philadelphia. Despite the aspirations expressed within the Harm Reduction narrative to open such a site, opposition from the Nimby (not in my backyard) narrative has, at the time of this research, successfully precluded such a step. Other narratives in the discourse include the Abstinence narrative opposing safe injection sites and the Social Justice narrative opposed to incarceration but also hesitant to wholeheartedly endorse the Harm Reduction narrative for its delayed advocacy of compassionate treatment of people who use drugs now that the face of the person who uses opioids is a white one. In addition to juxtaposing competing narratives against one another and considering their alignments, disagreements, and interactions, the authors consider absences and shared presuppositions. The social construction of the purported drug addict varies in some ways between and among the prevailing narratives; in other ways, all the narratives problematize "addiction" as an affliction that justifies techniques of discipline aimed at caring for and controlling the population.